2013
DOI: 10.1136/gutjnl-2012-304351
|View full text |Cite
|
Sign up to set email alerts
|

Keratin 19: a key role player in the invasion of human hepatocellular carcinomas

Abstract: ObjectiveKeratin (K)19, a biliary/hepatic progenitor cell (HPC) marker, is expressed in a subset of hepatocellular carcinomas (HCC) with poor prognosis. The underlying mechanisms driving this phenotype of K19-positive HCC remain elusive.DesignClinicopathological value of K19 was compared with EpCAM, and α-fetoprotein, in a Caucasian cohort of 242 consecutive patients (167 surgical specimens, 75 needle biopsies) with different underlying aetiologies. Using microarrays and microRNA profiling the molecular phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
246
3
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(270 citation statements)
references
References 36 publications
20
246
3
1
Order By: Relevance
“…15,21 The proportion of tissues expressing EpCAM in this study was a little higher than in earlier series, which reported EpCAM in 15.9%-48.7% of HCCs. [15][16][17][20][21][22][23] Kimura et al 23 have demonstrated that EpCAM expression was observed more often in HCC patients with HBV than in those with other etiologies, and the immunoreactivity of EpCAM has been found in up to 78% of HCC patients with HBV. The high proportion of HCC patients with HBV (74%) examined in this study might be a possible explanation for the higher EpCAMpositive rate.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…15,21 The proportion of tissues expressing EpCAM in this study was a little higher than in earlier series, which reported EpCAM in 15.9%-48.7% of HCCs. [15][16][17][20][21][22][23] Kimura et al 23 have demonstrated that EpCAM expression was observed more often in HCC patients with HBV than in those with other etiologies, and the immunoreactivity of EpCAM has been found in up to 78% of HCC patients with HBV. The high proportion of HCC patients with HBV (74%) examined in this study might be a possible explanation for the higher EpCAMpositive rate.…”
Section: Discussioncontrasting
confidence: 70%
“…These findings are in agreement with previous studies showing that expression level of EpCAM correlates with de-differentiation 11 and vascular invasion and is associated with the high AFP level in HCC. 20,21 The prognosis of patients with EpCAM-negative HCC is considered to be better than that of those with EpCAM-positive HCC. 11,[14][15][16]20,21 Although EpCAM expression was not found to be an independent predictor of survival in patients with HCC in this study, EpCAM expression was found to be associated with well-known unfavorable prognostic factors in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the phenotypic and genotypic profiles are similar to cholangiolo cellular carcinoma, thought to originate from hepatic progenitor cells 17,50,51 . A number of observations suggest that bile ductular (mixed)-type iCCAs together with cholangiolocellular carcinoma and CK19 + HCC represent a group of primitive liver cancers originating from hepatic progenitor cells, the different phenotype depending on the step of hepatic progenitor cell differentiation toward cholangiocytes or hepatocytes, in which neoplastic transformation occurs 17,20,[52][53][54] .…”
Section: Cells Of Originmentioning
confidence: 99%
“…K19 is known to be a marker of poor prognosis in HCC in several studies (19)(20)(21). Especially, K19 is reported as a key player in tumor invasion in HCC (22). However, the relationship between K19 and HCCCSCs is not fully understood.…”
Section: Introductionmentioning
confidence: 99%